2006
DOI: 10.1111/j.1365-2591.2006.01134.x
|View full text |Cite
|
Sign up to set email alerts
|

Influence of sodium hypochlorite on fracture properties and corrosion of ProTaper Rotary instruments

Abstract: Group 3 had significantly reduced resistance to cyclic fatigue compared with instruments in groups 1 and 2. The phenomenon of early fracture may be attributed to galvanic corrosion induced by the presence of dissimilar metals, where one acts as the cathode of a galvanic couple, established when the instrument is immersed in NaOCl solution. The NiTi alloy may acts as the anode and thus undergoes corrosion.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
90
1
2

Year Published

2008
2008
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 106 publications
(99 citation statements)
references
References 39 publications
6
90
1
2
Order By: Relevance
“…Sodium hypochlorite is an oxidative solution which breaks down polymer chains that cause structural deformations to a wide range of materials (Berutti et al, 2006;Yamauti et al, 2003). Some studies have confirmed the capacity of this substance to cause alterations during the process of disinfecting gutta-percha cones, especially when the solution is used at concentrations higher than 2.5% (Valois et al, 2005a,b).…”
Section: Introductionmentioning
confidence: 95%
“…Sodium hypochlorite is an oxidative solution which breaks down polymer chains that cause structural deformations to a wide range of materials (Berutti et al, 2006;Yamauti et al, 2003). Some studies have confirmed the capacity of this substance to cause alterations during the process of disinfecting gutta-percha cones, especially when the solution is used at concentrations higher than 2.5% (Valois et al, 2005a,b).…”
Section: Introductionmentioning
confidence: 95%
“…However, the potential for fracture of these instruments is still a main concern associated with their use 2,3) . Root canal curvature 4) , instrument geometry 5,6) , working speed 7) , the use of irrigant 8) , torque and sterilization procedures 9,10) , metal surface treatments 11) , heat treatment 12) , metallurgic characterization of the NiTi alloys 13) , and repeated clinical use 14,15) are factors that might enhance instrument fatigue. Moreover, these factors show different effects on the lifespans of different NiTi instrument systems.…”
Section: Introductionmentioning
confidence: 99%
“…A recent study showed that fi les immersed in 5.25 % of sodium hypochlorite had significantly less resistance to fracture when they underwent cyclic fatigue. 49 …”
Section: Irrigation and Irrigantsmentioning
confidence: 99%